Audit Technology And Standards Predict Documentation Quality Amidst Environmental Uncertainty: Teknologi Dan Standar Audit Memprediksi Kualitas Dokumentasi Di Tengah Ketidakpastian Lingkungan - Ismi Auliya Nur Rohmah; Novi Darmayanti; Dewi Kusmayasari (Academia Open, 2026)
General Background The integrity of the public accounting profession strictly requires thorough archiving practices to ensure accountability and compliance with professional regulations. Specific Background In Indonesia, the Audit Tool and Linked Archive System facilitates the structured preparation of electronic working papers. However, the excellence of this digital archiving relies heavily on the practitioner's adherence to professional rules and their proficiency with digital platforms. Knowledge Gap While previous studies extensively explore general practitioner performance, the specific determinants of electronic working paper integrity under unpredictable and complex client conditions remain underexplored. Aims This study examines how record completeness, professional rules, and platform utilization predict ATLAS-based archiving outcomes, analyzing external unpredictability as a moderating variable. Results Based on Partial Least Squares analysis of 100 practitioners, professional rules, platform utilization, and external unpredictability positively and significantly predict archiving outcomes. Record completeness shows no significant relationship. Furthermore, external unpredictability weakens the predictive power of professional rules while strengthening the role of digital platforms. Novelty This research demonstrates that sheer record availability is insufficient for accountability; instead, digital proficiency becomes the critical driver of archiving outcomes when navigating highly unpredictable external conditions. Implications Public Accounting Firms must prioritize digital proficiency training alongside strict regulatory compliance to maintain electronic archive integrity amidst complex client conditions. Highlights The sheer availability of working papers fails to guarantee archive integrity without systematic digital integration. Unpredictable client conditions weaken regulatory compliance but amplify the necessity of utilizing electronic platforms. The tested variables collectively account for 79.3 percent of the variance in electronic archiving outcomes. Keywords ATLAS Application; Audit Documentation; Auditing Standards; Environmental Uncertainty; Technology Utilization